Utilization of Ambulance Service Booking Applications As A Means Of Health Transportation For The Community In Pekanbaru City - Zaky, Abdul; Suryandartiwi, Wiwik; Hendriani, Sisi; Tonis, Marian; Nurhadi, Muhammad (Universitas Sahid Surakarta, 2025)
The role of technology will always be present in every community activity in the current 5.0 era. Technology plays an important role in sustaining life both socially, economically and in the health sector in society. One of the important health services today is ambulance services. Ambulance services that are integrated with technology can make it easier for people to access this service. The ambulance service application that has been designed can be utilized by the community for emergency or non-emergency needs. The community service activity carried out is technical guidance on ambulance service applications to youth groups in Tangkerang Selatan Village, Pekanbaru City. Community Service activities are carried out with the stages of preparation, implementation to members of the Tangkerang Selatan youth organization and evaluation and reporting of activities. The preparation activities have been carried out by designing an Ambulance Booking Application which has been carried out a function test and application feasibility test. The function test results state that the application has functioned properly and the feasibility test results state that it is feasible with a percentage of 100%. Based on the distribution of ambulances in hospitals and health centers in Pekanbaru City, there are 56 ambulances. This number can certainly be more considering the existence of ambulances owned by other organizations or institutions. FGD activities are carried out to team members with several students by making preparations related to activities. The implementation of community service activities was carried out to the Tangkerang Selatan youth organization where with this activity, the role of youth organizations was more optimal in the community. A total of 28 members of the Youth Organization and the Community attended this activity and were enthusiastically followed. The results of the evaluation of this activity were carried out by distributing post-tests to participants related to understanding the use of applications. The evaluation results showed that 75% strongly agreed, 18% agreed and 7% did not understand. Activity reporting begins with the proposal for Copyright on the Application named Pekanbaru Ambulance Booking System (PABS). The output of community service activities also produces videos uploaded on YouTube and scientific articles in National Accredited Journals.